Researches of biological activity of lectin-containing extracts of purple coneflower (Echinacea purpurea (L.) Moench.) - Поспєлов, С. В.; Шершова, С. В. (Scientific Progress & Innovations, 2012)
The biological activity of the lectin containing extracts of Echinacea purpurea and their components by testing on watercress salad sprouts was investigated. It’s established that the lectins that contained in extracts of all commodities, depressing the test system at a concentration of 10% -0.1%. In further dilution of extracts of leaves and stems of Echinacea purpurea did not significantly affect or inhibit the growth of shoots of watercress salad. Complete extract of rhizomes with roots in concentrations of 10-1-10-4 slightly stimulated, but in subsequent dilution of extract – inhibited the test object. Testing extracts inflorescences of Echinacea purpurea showed stimulation shoots to 25% of control at concentrations 10-2-10-8%. The effect of protein components more depressing than stimulating the test object was established.